Exploring the circular prospects of cashew nutshells and avocado seeds as potential adsorbents for onboard natural gas storage - Theresia J. Riwa; Silvia J. Mushi; Makungu M. Madirisha; Petro E. Mabeyo; Edgar C. Mapunda (Next Materials)
Natural gas (NG), known for its eco-friendly energy attributes, faces challenges such as low volumetric density, leakage susceptibility, and explosion risks during storage and transport. To narrow this gap, this study reports on the potential of bio-based adsorbents from cashew nut shells (CNS) and avocado seeds (AVS) as an alternative approach for the onboard storage of NG. CNS and AVS were characterized to determine moisture content, volatile matter content, ash content, and fixed carbon content. Additionally, the study determined the optimal loading of activating agents to produce activated carbons (ACs). ACs were produced through a dual process involving simultaneous chemical activation and carbonization. In the chemical activation phase, a sample of either cashew nut shells (CNS) or avocado seeds (AVS) was impregnated with phosphoric acid at various ratios. Subsequently, the properties of the ACs, including surface area, pore volume, and X-ray diffraction (XRD), were evaluated. The NG adsorption capacity of the ACs was assessed, and Freundlich and Langmuir isotherm adsorption equations were derived to elucidate the NG adsorption behavior on the ACs. The results revealed that the proximate analysis of CNS and AVS showed low moisture content (6.48% and 8.91%), high volatile matter (80.21% and 73.09%), low ash content (1.48% and 4.71%), and high fixed carbon (13.65% and 15.59%), indicating suitability for AC formulations. During synthesis, adding phosphoric acid to AVS or CNS in a 1:1 ratio resulted in significantly larger surface areas and pore volumes in the produced ACs. X-ray diffraction analysis of the ACs produced from CNS or AVS with phosphoric acid added at a 1:1 ratio indicated a broad diffraction background and a predominantly amorphous structure. The performance of the ACs in the adsorption of NG demonstrated that ACs produced from 1:1 mixtures of CNS with phosphoric acid and AVS with phosphoric acid exhibited higher adsorption capacities, 0.038 g/g and 0.031 g/g, respectively, at a low pressure of 5 bar, showcasing a novelty of this study. Furthermore, the Freundlich equation test yielded a constant R² exceeding 0.9, with positive adsorption intensity and adsorption capacity values, indicating a favorable fit for the model. In contrast, the Langmuir equation test resulted in a constant R² exceeding 0.9, but the adsorption capacity exhibited negative values, leading to inconclusive explanations. These findings affirm that bio-wastes can be an effective source of adsorbents for onboard natural gas storage , suggesting a means to reduce the take-dispose model and promote a circular economy in the energy sector.